Penerapan Sikap Tanggung Jawab Siswa pada Mata Pelajaran IPS Kelas V di Sekolah Dasar - Osy, Tika Olivia; Supriatna, Encep (Didaktika, 2022)
Attitude education in this day and age is very important because attitudes are formed around the environment. Social Science subjects teach that a good attitude of responsibility certainly needs to be applied in everyday life, but the attitude is not realized properly. This approach to research uses qualitative approaches and the methods used are case study methods. Research techniques in the form of data collection techniques and data analysis techniques, data collection techniques used are observations, interviews, and documentation, while data analysis techniques to compile data findings are by way of the first 3 flows of data reduction, data presentation, and conclusion withdrawal. The instruments used are observation and interview. From the results of the research conducted, it was obtained that from 13 students of fifth grade, 5 students lacked the attitude of responsibility in the classroom and learning Social Sciences, during the learning process students showed that, the attitude of responsibility was less applied, namely the lack of attitude of responsibility towards the given task, the lack of responsibility towards the time of the collection of tasks,  The absence of creative ideas during learning, lack of socialization of responsibility by teachers. The measures implemented are also less maximal, namely the lack of introduction to the attitude of responsibility, the drive to be responsible, and praise for responsibility. The obstacles experienced are the character of students, different backgrounds, different abilities, understanding of attitudes of responsibility, and lack of care for parents and students' learning outcomes.